Experimental investigation on the effect of biomimetic wingtips on aerodynamics of wings - Siddiqui, Naseeb Ahmed (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Experiments on the relative merits and demerits of slotted wingtips mimicking bird's primary feathers have been performed. The real emargination length of feather tips, their flexibility and curved shapes during cruise are considered in the present study. The experiments were performed at a Reynolds number of 3.5 x 105 on a low aspect ratio symmetric flat plate half wing. Lift, drag and pitching moments were measured using a six component aerodynamic balance. Results from more than forty different wing tip models were compared which proved the superiority of the rigid curved tips. It is observed that both flexible and rigid curved tips reduce the drag but the rigid curved tip performs the best by increasing the L/D ratio by 20% that proposes increment in the range of propeller airplane around 7.8%, for jet-airplane about 9% and the climb rate around 13.5%. Rigid curved tip has some more advantages over flat multi tips configuration. It can provide performance benefits by reducing the span of wing, a design factor for runway and airplane handling. Similarly, due to decrease in vortex intensity the distance and danger posed to the preceding airplane can be lessened which ultimately results in increased frequency of airplane traffic. Prediction of better performance compared to staggered wingtip seems clear from the values. Performance parameters like thrust, power, range, endurance, rate of climb, velocity and gliding angle of a subsonic airplane depends on L/D. The long held view that elasticity of bird feather has to do with drag reduction is still true in this experiment with some improvement in aerodynamic coefficients.